2023
DOI: 10.21203/rs.3.rs-2547880/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting-State Functional Connectivity Changes in Older Adults with Sleep Disturbance and the Role of Amyloid Burden

Abstract: Sleep and related disorders could lead to changes in various brain networks, but little is known about the role of amyloid β (Aβ) burden—a key Alzheimer’s disease (AD) biomarker—in the relationship between sleep disturbance and altered resting state functional connectivity (rsFC) in older adults. This cross-sectional study examined the association between sleep disturbance, Aβ burden, and rsFC using a large-scale dataset from the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Sample included 489 individua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Additionally, the observation that shorter sleep duration was associated with greater salience network connectivity may be consistent with findings indicating that insomnia symptoms (which are reflective of reduced sleep duration or quality) are associated with higher insula connectivity, a critical part of the salience network ( Chen et al, 2014 , Cheng et al, 2022 ). It is also in line with a recent investigation among individuals across the AD spectrum that found that subjective sleep disturbances were associated with hyperconnectivity within the salience network in individuals who were amyloid positive vs. negative ( Kim et al, 2023 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, the observation that shorter sleep duration was associated with greater salience network connectivity may be consistent with findings indicating that insomnia symptoms (which are reflective of reduced sleep duration or quality) are associated with higher insula connectivity, a critical part of the salience network ( Chen et al, 2014 , Cheng et al, 2022 ). It is also in line with a recent investigation among individuals across the AD spectrum that found that subjective sleep disturbances were associated with hyperconnectivity within the salience network in individuals who were amyloid positive vs. negative ( Kim et al, 2023 ).…”
Section: Discussionsupporting
confidence: 89%
“…Finally, Model 3 (fully adjusted) tested whether the independent association of TVPA, TST, and SE with rsFC were moderated by PET amyloid status (which can influence relationships among sleep, physical activity, and resting-state connectivity ( Kim et al, 2023 , Lin et al, 2020 , Pruzin et al, 2022 )), by additionally including an interaction term PET amyloid status x [PA or sleep measure]) in the fully adjusted model. Non-significant interaction terms between diagnosis and PET amyloid status with PA and sleep metrics are not reported.…”
Section: Methodsmentioning
confidence: 99%